Persepsi guru tentang peranan pengetua sebagai pemimpin pengajaran : kajian di beberapa buah sekolah menengah di bahagian Kuching - Haminah, Binti Lek (Universiti Malaysia Sarawak (UNIMAS), 1998)
The aim of this study is to examine the role of the principal as instructional leaders in schools. It specifically (i) identifies teacherʼs perception regarding the principalʼs role as instructional leaders, (ii) examines differences in respondentsʼ perceptions of the role of principals as instructional leaders based on the background characteristics of the respondents and schools, and (iii) analyses respondentsʼ ranking of the various roles of principals as instructional leaders. The respondents for the study comprised 217 teachers from 4 secondary schools in Kuching Division.